Krankenstein's crazy house of horror - Strong, Jeremy (London : Puffin, 2009)
Charlie and his great mate Ben have landed in a spooky House of Horror- all because of Charlie's new pyamas! The mean old Stitcher and her stinky sidekick Grumpfart are planning to take revenge on the entire world.
Keywords: Horror fiction; Monster -- Fiction